PERBEDAAN SAHAM PERUSAHAAN TRANSPORTASI SEBELUM DAN PASCA PENGUMUMAN PANDEMI COVID-19 DI BURSA EFEK INDONESIA. - Putu Novia Hapsari Ardianti; Kadek Apriada; Ni Kadek Ely Pramitasari (Jurnal Widya Akuntansi dan Keuangan, 2024)
The impact of the Covid-19 pandemic is not only detrimental to human health but also detrimental to the economic sector. The economy is the most important factor in human life. In addition, Covid-19 also affects stock price, stock trading volume, and stock return. This study aims to determine the difference between stock price, stock trading volume, and stock return before and during the Covid-19 pandemic in transportation companies listed on the Indonesia Stock Exchange (IDX). The sampling method used is purposive sampling. Of the 46 companies listed on the Indonesia Stock Exchange, 26 companies met the criteria and were sampled. The analysis method used in this study was the Wilcoxon signed-rank test. The results of this study show that there is a significant difference in stock prices between before the pandemic and during the Covid-19 pandemic, while the results of the study on stock trading volume and stock returns show that there is no significant difference between before the pandemic and during the Covid-19 pandemic. Further research is suggested to add other variables such as market capitalization and market frequency to get better and more accurate results